Rediscovery of Myrmecolacidae from China with a new Myrmecolax species and a checklist of Chinese twisted-wing parasite (Insecta: Strepsiptera) - Zheng, Xuhongyi; Zhou, Changfa (Zootaxa, 2025)
Myrmecolacidae is a poorly documented family of Strepsiptera in China, previously only three specimens were gathered from this country. In this study, we describe Myrmecolax aranealis sp. nov. from Yunnan Province, southwestern China, after nearly 40-years hiatus. The new species can be distinguished by: (1) comparatively large body size (2.0 mm), (2) an exceptionally slender flabellum on antennomere III that extends nearly to the apex of antennomere VII, and (3) distinct hindwing venation. In addition, an updated checklist of Chinese Strepsiptera, and a revised taxonomic key to Asian Myrmecolax species are provided.